Design and Implementation of Temperature Detection Gates and Hand Sterilization for Covid-19 Prevention - Agus Ulinuha; Muhammad ‘Alim Alfaridzi (Urecol Journal. Part E: Engineering, 2021)
One of the efforts to reduce the transmission of Corona Virus Disease-19 (Covid-19) is by detecting body temperature and disinfection. Detection of body temperature is carried out as an effort to identify sufferers of Covid-19 so it is necessary to prevent them to get together with other people. Manual temperature measurement may cause burnout of staff doing this task and reduced accuracy. Therefore it is necessary to develop an automatic temperature measurement system and display the data be easily observed. Apart from measuring body temperature, another effort to prevent Covid-19 infection is to disinfect the hands. The disinfection process can be done by automatically spraying the disinfectant gel on the hands. The two processes are carried out sequentially, after the body temperature is measured and does not exceed the limit, then the disinfection process is carried out. This procedure is implemented in a gate equipped with two blades with the first blade opening when the body temperature does not exceed the limit, followed by the opening of the second blade after the automatic disinfection of the hand. The procedures are done automatically without touch to minimize physical contact. For the development of the system, an Arduino Mega 2560 microcontroller is needed, 3 MLX90614, 3 HC-SR04 sensors, 3 e18-d80nk, 1 relay, 1 DC motor pump and 2 DC blade actuator motors. The allowable body temperature limit can be determined by manual setting. Operationally this system has been tested and demonstrated the ability to work as desired, including spraying disinfectant gel. For verification of temperature measurements, there was an average deviation of 0.018% from the measurement by the sensor to the temperature measured with thermogun.